Predictive Analysis of NLR, Absolute Lymphocyte Count, and CT-Value on The Severity of Covid-19 Patients: Analisis Prediksi NLR, Absolute Lymphocyte Count, dan CT-Value Terhadap Derajat Keparahan Pasien Covid-19 - Bastiana; Donastin, Adyan; Arista, Devi Maya; Surya, Prima Ardiansah (Universitas Muhammadiyah Sidoarjo, 2022)
Laboratory parameters in Covid-19 patients may have a relationship with the clinical severity of the patient on arrival. This study aims to Analyzing the relationship between NLR, ALC, and CT values with the clinical severity of Covid-19 patients on arrival. A total of 101 subjects were collected from medical records of RSI Jemursari Surabaya from April to September 2020. The correlation laboratory parameters (NLR, ALC, and CT-value) with the severity of Covid-19 patients (mild, moderate, severe and critical) were analyzed using One Way Anova and Kruskal Wallis. The relationship of NLR with severity (p-value=0.143), ALC with severity (p-value=0.165), and CT-value with severity (p-value= 0.987). Patients with COVID-19 tend to have a high NLR in all clinical conditions. The mean value of the ALC was within normal limits for all degrees of severity. There is no significant relationship between NLR, ALC, CT-value with the severity of Covid-19 patients.